THE IMPORTANCE OF USING DIGITAL EDUCATIONAL RESOURCES IN THE ORGANIZATION OF INDEPENDENT EDUCATION OF TEACHING STAFF (IN THE EXAMPLE OF THE ENGLISH LANGUAGE OF THE ENGINEERING FIELD) - Kudratov Siroj Normamat ugli (PEDAGOGS, 2024)
Abstract: In this article, we consider the importance of using digital learning resources to organize and improve self-learning of teachers, focusing on the example of English in the field of engineering. By exploring the benefits of digital tools, the application of these resources in engineering, and the transformative impact on professional development, we equip faculty with the skills and knowledge that digital education needs to excel in their fields we would like to emphasize the important role of equipment.